2013
DOI: 10.2174/1874834101306010025
|View full text |Cite
|
Sign up to set email alerts
|

Review of Hole Cleaning in Complex Structural Wells

Abstract: Abstract:Complex structural wells are widely used in the development of marine oilfield, old oilfield and low permeable oilfield. However, poor hole cleaning is often occurred in the highly-deviated sections and horizontal sections of the complex structural wells, which affects rate of penetration and downhole safety.The methods to study cuttings transport can be normally divided into four types: 1) experimental observations, 2) CFD simulations, 3) theoretical correlations and models and 4) field tests. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…The critical analysis of the result revealed that although annulus cutting concentration profile decreases as GOR which epitomizes gas volume increases, greater change occurred when GOR was between 0.3 -8.0 for only 0.27m 3 /s and 0.57m 3 /s. The result is in agreement with Leising and Waiton [8] that there exists increase in turbulence by the presence of limited amount of gas and helps the solids in suspense. Thus, the greater increase in hole cleaning performance between GOR 0.3 -8 can be attributed to limited amount of gas volume which primarily increase turbulence and expansion as it near the surface, annular velocity simultaneously increased.…”
Section: Effect Of Gas/liquid Ratio (Gor)supporting
confidence: 91%
See 1 more Smart Citation
“…The critical analysis of the result revealed that although annulus cutting concentration profile decreases as GOR which epitomizes gas volume increases, greater change occurred when GOR was between 0.3 -8.0 for only 0.27m 3 /s and 0.57m 3 /s. The result is in agreement with Leising and Waiton [8] that there exists increase in turbulence by the presence of limited amount of gas and helps the solids in suspense. Thus, the greater increase in hole cleaning performance between GOR 0.3 -8 can be attributed to limited amount of gas volume which primarily increase turbulence and expansion as it near the surface, annular velocity simultaneously increased.…”
Section: Effect Of Gas/liquid Ratio (Gor)supporting
confidence: 91%
“…Sun et al [8] carried out review of research works in hole cleaning in complex structural wells on the effects of flow rate, inclination, mud rheology, drillpipe rotation and other factors on hole cleaning and some correlations and models were developed. The major areas identified as gab for future experimental research study is the use of flow loop that depicts the real cuttings transport under downhole conditions including formation fluid influx, wellbore collapse and the annular temperature.…”
Section: Fig 1: Schematic Diagram Of a Close Flow Loopmentioning
confidence: 99%
“…The existing problems and characteristics of these correlations and models were summarized by [15]. Theoretical models and correlations mainly applied to calculate cuttings bed height, critical velocity to provide the guidance for the design of hydraulic parameters and the effects of flow rate, inclination, mud rheology, drill pipe rotation and other factors on hole cleaning, in addition, CFD simulations was applied [16]. In real time drilling, mud properties in any type of wells rather are complex with numerous parameters.…”
Section: Introductionmentioning
confidence: 99%